Supporting second language acquisition of bilingual preschool children through professionalization of caregivers in specialized preschool programs - Boese, Jannika; Busch, Julian; Leyendecker, Birgit; Scherger, Anna-Lena (Frontiers in Psychology, 2023)
The aim of the present study was to investigate the effectiveness of a training program on language support strategies and dialogic reading for caregivers working in specialized preschool programs. These programs serve children without a regular childcare place who grow up with one or more languages other than German as the environmental language. Recent studies investigating the development of children attending these programs found only moderate improvements in German receptive language skills, while language support quality of the programs was rated as average. We assessed receptive second language competencies in vocabulary and grammar of n = 48 children and language support competencies of n = 15 caregivers using an interventional pre-posttest design. Receptive vocabulary skills of children supported by trained caregivers (intervention group) were compared to children supported by untrained caregivers (control group, n = 43). We found that both children’s and caregivers’ competencies increased from pre- to posttest, whereas the control group’s receptive vocabulary skills did not increase noticeably. The caregivers’ language support competencies influenced the increase of children’s receptive grammar but not vocabulary skills. The comparison between the intervention group and control group consistently showed no effect of group membership on children’s receptive vocabulary acquisition over time. Since the control group data came from a secondary analysis, only receptive vocabulary skills could be compared. The preliminary results of our study suggest that a caregivers’ training on language support strategies and dialogic reading in everyday educational situations support bilingual children's grammar acquisition.